Coordination of coupled systems of systems with quadratic approximation ⁎. Issue 3 (2019) - Wenzel, Simon; Engell, Sebastian
Abstract: The process industries becomes increasingly digital, integrated, and connected. Chemical production sites consist of many subsystems which are tightly interconnected and physically coupled by flows of material and energy. Coordination of these systems of systems is essential but challenging. Various barriers prohibit a joint optimization of the overall system. One of the barriers results from the complex management structure of these systems which does not allow for the exchange of all necessary information for a holistic formulation and solution of the optimization problem. Market-like coordination is one way to address this challenge by establishing a micro-market for shared resources between the competing subsystems. However, market-like coordination is known for its slow rate of convergence. Using quadratic approximation for an improved rate of convergence was proposed in Wenzel et al. (2016). In this contribution, we present an extension of this algorithm and apply it to a number of randomly generated medium- to large-scale test problems. The performance of the algorithm is compared to the performance of subgradient-based coordination and to the performance of the Alternating Direction Method of Multipliers (ADMM).